2008
DOI: 10.3758/mc.36.7.1262
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing the central bottleneck after single-task practice in the psychological refractory period paradigm: Evidence for task automatization and greedy resource recruitment

Abstract: In this research, the controversial issue of whether the central bottleneck can be bypassed through task automatization was investigated. To examine this issue, participants received six single-task practice sessions with an auditory-vocal task (low vs. high pitch). We then assessed dual-task performance using the analytically tractable psychological refractory period (PRP) paradigm, in which the highly practiced auditory-vocal task was presented as Task 2, along with an unpracticed visual-manual Task 1. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
121
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(132 citation statements)
references
References 37 publications
6
121
4
1
Order By: Relevance
“…A third modification was to increase the sample size (i.e., 20 young participants instead of six), so that the prevalence of bottleneck bypassing could be better established. These measures appear to have been very successful: Maquestiaux et al (2008) reported several converging indicators of bottleneck bypassing in the vast majority of participants (17 out of 20). Specifically, for the bypassers, the mean PRP effect on Task 2 was only 166 ms despite the long duration of Task 1 (641 ms); response reversals were very frequent at the shortest SOA (66.1%), and the effects of increasing the duration of Task-1 processing stages up to and including the central stage (by 173 ms) did not carry over fully onto RT2 at short SOAs (the percentage of carryover was only 34.1%).…”
Section: Can the Central Bottleneck Be Bypassed Through Extensive Pramentioning
confidence: 99%
See 1 more Smart Citation
“…A third modification was to increase the sample size (i.e., 20 young participants instead of six), so that the prevalence of bottleneck bypassing could be better established. These measures appear to have been very successful: Maquestiaux et al (2008) reported several converging indicators of bottleneck bypassing in the vast majority of participants (17 out of 20). Specifically, for the bypassers, the mean PRP effect on Task 2 was only 166 ms despite the long duration of Task 1 (641 ms); response reversals were very frequent at the shortest SOA (66.1%), and the effects of increasing the duration of Task-1 processing stages up to and including the central stage (by 173 ms) did not carry over fully onto RT2 at short SOAs (the percentage of carryover was only 34.1%).…”
Section: Can the Central Bottleneck Be Bypassed Through Extensive Pramentioning
confidence: 99%
“…Therefore, we tackled this issue in the present study, taking advantage of procedures from previous studies that have successfully shown bottleneck bypassing in young adults (e.g., Maquestiaux et al, 2008;Ruthruff, Van Selst, et al, 2006). Specifically, 12 older adults participated in a PRP experiment strictly identical to Experiment 1 of Maquestiaux et al (2008), which was carried out with 20 young adults. In the present study, we utilized the data from the young adults in Maquestiaux et al as a baseline to compare the new data from 12 older adults in the identical procedure.…”
Section: Goals Of the Current Studymentioning
confidence: 99%
“…In fact, Schumacher et al (2001) found that dual-task and mixing costs were eliminated after five practice sessions of about 1,000 dual-task trials and 3,000 single-task trials (see also Hazeltine Teague, & Ivry, 2002;Liepelt, Strobach, Frensch, & Schubert, in press;Maquestiaux, Laguẽ-Beauvais, Ruthruff, & Bherer, 2008;Ruthruff, Van Selst, Johnston, & Remington, 2006;Strobach, Frensch, & Schubert, 2008; but see Liepelt, Fischer, Frensch, & Schubert, 2011, for boundary conditions of this finding). That is, RTs were similar in dual-task trials and single-task trials of the mixed and single-task blocks.…”
Section: Introductionmentioning
confidence: 99%
“…However, to reach near-perfect, or even perfect, time-sharing, changes within the component tasks would also have to occur. In the last decades, a number of studies have suggested that this sort of component task optimization may result from dual-task as well as single-task practice (Ahissar et al, 2001;Maquestiaux, Laguë-Beauvais, Bherer, & Ruthruff, 2008;Ruthruff et al, 2001Ruthruff et al, , 2003Ruthruff, Van Selst, Johnston, & Remington, 2006;Sangals, Wilwer, & Sommer, 2007;Van Selst et al, 1999). However, it is relatively unclear which specific stages within the component tasks are optimized and shortened as a result of dual-task practice: the initial perception, central response-selection, or final motor stages, or a combination of these stages (Pashler & Baylis, 1991).…”
mentioning
confidence: 99%